Efektifitas Pemberian Jus Jambi Terhadap Kadar Hemoglobin Ibu Hamil Trisemester II dengan Anemia - Dwi Estuning Rahayu (Poltekkes Kemenkes Malang, 2020)
Pregnant women who suffer from anemia are at risk of miscarriage, babies born prematurely, babies with low birth weight, and bleeding before and after delivery. Handling anemia in pregnant women, there are 2 ways to do it, they are pharmacology and non pharmacology. non pharmacological ways of anemia and prevention by consuming beets, guava, and spinach juice. The study aims to determine the effectiveness of giving guava juice, beets and spinach juice on hemoglobin levels in second trimester pregnant women with anemia. The research method uses The One Group Pretest Posttest Design. The population is second trimester pregnant women with anemia at Aura Syifa Kediri Hospital. The number of samples was 30 trimester II pregnant women with anemia with a purposive sampling method. Bivariate analysis techniques using paired t test and multivariate analysis using Oneway Anova, p equal 5 percent. The instrument used was the Easy Touch Blood Hemoglobin. Provision of guava juice, p value is smaller than 0.001, p value is smaller than, beet juice, p value is smaller than 0.001, p value lebih kecil dari, and spinach juice, p value is smaller than 0.001, p value is smaller than are effective in increasing Hb levels second trimester pregnant women with anemia. Oneway Anova analysis showed the average difference in Hb levels of spinach juice 2.50 gr for dl, 2.15 gr for dl beet juice, and guava juice 1.82 gr for dl. This means that the use of spinach juice is higher in raising Hb levels compared to beet juice and guava juice. It is expected that the provision of spinach juice, guava and beets can be an alternative in preventing and managing anemia in pregnant women.